Effects of substituting Nb with V on thermal analysis and biocompatibility assessment of quaternary NiTiNbV SMA - Balci, Esra; Dagdelen, Fethi; Qader, Ibrahim Nazem; Kok, Mediha (Springer Heidelberg, 2021)
The developed NiTi-based shape memory alloys are the most widely used materials in commercial applications due to shape memory effect and superelasticity. In this study, it is aimed to investigate the thermal, microstructural, and corrosion behavior of NiTiNb SMA by alloying with different composition of vanadium. The alloys with nominal composition Ni27Ti50Nb23-xVx (x=1, 2, 5) were manufactured by the arc-melting device under an argon gas atmosphere. The DSC measurements showed that the alloys are low-temperature shape memory alloys and the changes in the composition have not made a significant effect on the phase transformation temperatures. According to thermodynamics parameters, such as enthalpy and entropy changes, it is found that the alloy with 2 (at.%) of vanadium has more stability compared with the other SMAs. The microstructural analysis reveals that the Ni27Ti50Nb21V2 (at.%) alloy has a different dendritic microstructure, whereby, the mapping shows that the dendritic of the alloy almost consists of Nb, while the other alloys Ti are the host element in the dendritic microstructure. It is realized that the manufactured alloys have less biocompatibility since they have shown a high corrosion rate compared to equiatomic NiTi SMAs.